2017
DOI: 10.7554/elife.28468
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary routes to biochemical innovation revealed by integrative analysis of a plant-defense related specialized metabolic pathway

Abstract: The diversity of life on Earth is a result of continual innovations in molecular networks influencing morphology and physiology. Plant specialized metabolism produces hundreds of thousands of compounds, offering striking examples of these innovations. To understand how this novelty is generated, we investigated the evolution of the Solanaceae family-specific, trichome-localized acylsugar biosynthetic pathway using a combination of mass spectrometry, RNA-seq, enzyme assays, RNAi and phylogenomics in different n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
263
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 98 publications
(280 citation statements)
references
References 98 publications
(178 reference statements)
12
263
0
Order By: Relevance
“…RNAseq analysis was done essentially according to Moghe et al (2017). Total RNA was extracted from leaf and flower parts at different stages of development using the Total RNA Isolation Kit from Omega.…”
Section: Rnaseq Analysismentioning
confidence: 99%
“…RNAseq analysis was done essentially according to Moghe et al (2017). Total RNA was extracted from leaf and flower parts at different stages of development using the Total RNA Isolation Kit from Omega.…”
Section: Rnaseq Analysismentioning
confidence: 99%
“…The acyl chains are branched or straight and are proposed to be derived from amino acid or fatty acid metabolism, respectively (Walters and Steffens, 1990; Kroumova and Wagner, 2009; Ning et al, 2015). Acylsugar cores from Solanaceae species are primarily sucrose or sometimes glucose (King et al, 1986; King and Calhoun, 1988; Maldonado et al, 2006; Ghosh et al, 2014; Liu et al, 2017; Moghe et al, 2017; Leong et al, 2019). Solanum lanceolatum is a published exception, accumulating acylated disaccharide cores that contain myo -inositol bound to glucose or xylose (Herrera-Salgado et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Solanum lanceolatum is a published exception, accumulating acylated disaccharide cores that contain myo -inositol bound to glucose or xylose (Herrera-Salgado et al, 2005). Moghe and colleagues screened acylsugars in plants across the Solanaceae family (Moghe et al, 2017). One species – the South American fruit crop Solanum quitoense – produced unusual acylsugars that yielded lower signals of fragment ions generated in a mass spectrometer than acylsucroses or acylglucoses from other members of the Solanaceae (Hurney, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second challenge involves identifying the thousands of metabolites observed in MS data from highly sensitive MS instruments. A recent study found evidence for >300 compounds of a single metabolite class (acylsugars) in a single leaf surface extract (Moghe et al, 2017). …”
mentioning
confidence: 99%